Universal PLC trainer - Taman, Ishak; Jambari, Hanifah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The development of the Universal PLC Trainer aims to simplify and accelerate the understanding of fourth-semester students in the DEE and DJK programs enrolled in the DEJ40033 PLC & Automation course. This teaching kit is universal and portable, equipped with essential components for practical exercises in conventional wiring, PLC programming, electropneumatic, and industrial automation. Additionally, it features a Human Machine Interface (HMI) function to monitor input and output operations through controls such as touchscreen, voice control, and motion control. The HMI can also be programmed to display operation status using indicator lights, buzzers, and simulated LED displays. The kit is designed with a neat component layout, user-friendly interface, and high safety standards. Circuit connections are implemented via a plug and play system, making the process easier, faster, and safer. This innovation addresses the shortcomings of existing trainers, which are often disorganized, unsafe, and fail to meet practical syllabus requirements. The Universal PLC Trainer enhances the quality of teaching and learning, reduces instructional time, and improves students' comprehension. It is also cost-efficient, as its construction does not require additional external equipment. Students are more motivated as this learning method is engaging, portable, and systematically arranged according to theoretical topics. This innovation not only has a significant impact on students and lecturers but also holds potential for use by other organizations, such as Community Colleges, Vocational Colleges, and individuals interested in exploring the field of Programmable Logic Controllers (PLC). With the potential for broad application, the Universal PLC Trainer is a significant and innovative discovery in the field of engineering education and TVET.